2018
DOI: 10.1039/c8tc04297g
|View full text |Cite
|
Sign up to set email alerts
|

A highly sensitive and flexible capacitive pressure sensor based on a micro-arrayed polydimethylsiloxane dielectric layer

Abstract: A flexible pressure sensor with high sensitivity has been proposed which consists of a typical sandwich structure by integrating a PDMS substrate with a micro-arrayed PDMS dielectric layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
90
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(94 citation statements)
references
References 36 publications
1
90
1
Order By: Relevance
“…These demonstrate the lack of functionality of the sensing materials, which limit their practical applications [ 16 ]. Recently, a variety of flexible tactile sensors have been developed based on different operational sensing mechanisms, including piezoresistive-based [ 17 , 18 ], piezoelectric-based [ 19 , 20 ], capacitive based [ 21 , 22 ], and optical based sensors [ 23 ]. Among them, flexible piezoresistive sensors, which are based on transducing the external mechanical pressure into resistance variation outputs, have attracted considerable attention, due to their simple structure, low-cost, and easy signal processing [ 9 , 24 ].…”
Section: Background Studymentioning
confidence: 99%
“…These demonstrate the lack of functionality of the sensing materials, which limit their practical applications [ 16 ]. Recently, a variety of flexible tactile sensors have been developed based on different operational sensing mechanisms, including piezoresistive-based [ 17 , 18 ], piezoelectric-based [ 19 , 20 ], capacitive based [ 21 , 22 ], and optical based sensors [ 23 ]. Among them, flexible piezoresistive sensors, which are based on transducing the external mechanical pressure into resistance variation outputs, have attracted considerable attention, due to their simple structure, low-cost, and easy signal processing [ 9 , 24 ].…”
Section: Background Studymentioning
confidence: 99%
“…They refer to the organized arrays of water droplets that form when humid air comes in contact with cold solid or liquid surfaces.
Fig. 4Patterned elastomer based strain/pressure sensor with varied approaches (i) Conducting polymer induced enhanced conductivity(Reproduced by permission from [49] Copyright 2014, Wiley ) (ii) rGO/PDMS patterned (Reproduced by permission from [58] Copyright 2016, Springer ) (iii) Plasma induced electrode defined on wrinkled PDMS (Reproduced by permission from [50] Copyright 2018, Royal Society of Chemistry ) (iv) Compound elastomer pattern with complimentary rGO/PDMS films (Reproduced by permission from [47] Copyright 2014, Wiley ) (v) Patterned PDMS with breath figures (Reproduced by permission from [51] Copyright 2014, IOP science )
…”
Section: Evolution Of Sensor Device Architecturementioning
confidence: 99%
“…for the last many decades. [8][9][10][11][12][13][14][15][16][17] In the past, many authors, including our group have reported lead-based materials for suitable pressure sensors in the low and high-pressure range, where a signicant change in dielectric constant, piezoelectric coefficient and capacitive reactance was observed as a function of pressure. [1][2][3][5][6][7]13,[18][19][20][21][22][23][24][25][26] However, the effect of pressure on change in dielectric constant was not as signicant that it can be realized for real high-pressure sensor devices.…”
Section: Introductionmentioning
confidence: 99%